Multiple inflammatory biomarkers in relation to cardiovascular events and mortality in the community - Schnabel, Renate B; Yin, Xiaoyan; Larson, Martin G; Yamamoto, Jennifer F; Fontes, João D; Kathiresan, Sekar; Rong, Jian; Levy, Daniel; Keaney, Jr, John F; Wang, Thomas J; Murabito, Joanne M; Vasan, Ramachandran S; et al. (Arteriosclerosis, thrombosis, and vascular biology, 2013)
Evidence suggests that chronic low-grade inflammation and oxidative stress are related to cardiovascular disease (CVD) and mortality. We examined 11 established and novel biomarkers representing inflammation and oxidative stress (C-reactive protein, fibrinogen, interleukin-6, intercellular adhesion molecule-1, lipoprotein-associated phospholipase-A2 [mass and activity], monocyte chemoattractant protein-1, myeloperoxidase, CD40 ligand, P-selectin, and tumor necrosis factor receptor II [TNFRII]) in relation to incident major CVD and mortality in the community. We studied 3035 participants (mean age, 61 ± 9 years; 53% women). During follow-up (median, 8.9 years), 253 participants experienced a CVD event and 343 died. C-reactive protein (hazard ratio [HR] reported per SD ln-transformed biomarker, 1.18; 95% confidence interval [CI], 1.02-1.35; nominal P=0.02) and TNFRII (HR, 1.15; 95% CI, 1.01-1.32; nominal P=0.04) were retained in multivariable-adjusted models for major CVD, but were not significant after adjustment for multiple testing. The biomarkers related to mortality were TNFRII (HR, 1.33; 95% CI, 1.19-1.49; P<0.0001), ICAM-1 (HR, 1.24; 95% CI, 1.12-1.37; P<0.0001), and interleukin-6 (HR, 1.25; 95% CI, 1.12-1.39; P<0.0001). The addition of these markers to the model, including traditional risk factors, increased discrimination and reclassification for risk of death (P<0.0001), but not for CVD. Of 11 inflammatory biomarkers tumor necrosis factor receptor II was related to cardiovascular disease and mortality in the Framingham Heart Study. The combination of TNFRII with C-reactive protein in relation to CVD and with interleukin-6 to mortality increased the predictive ability in addition to CVD risk factors for total mortality but not for incident CVD.